Penerapan Peradilan Adat Berbasis Kuasi Yudisial Dalam Memutus Sengketa Adat - Al Araf Assadallah Marzuki (Universitas Batanghari Jambi, 2020)
The customary court is not a judicial institution that can decide a dispute with the direction of justice as in the national court so that recognition of customary decisions does not get permanent legal force which results in legal uncertainty in dispute resolution through customary court institutions. Thus, there is an idea that is offered in this research that implements customary courts as quasi-judicial in resolving customary disputes. Through normative juridical research, it is found that: first, the position of customary courts is only limited to deliberative dispute resolution, and in the judicial hierarchy its position is not recognized. Second, the quasi-judicial model that can be applied in customary courts can emulate KPPU in deciding disputes where to obtain permanent legal force, the KPPU's decision needs to be ruled by a district court, and if some object to the verdict, they can file an objection legal remedy in the domestic court. a period of 14 days from receipt of the decision on the parties.